Modern requirements to vocational training experts on economic cybernetics - SMILJANETS, Elena (Continuing Professional Education: Theory and Practice, 2019)
In article tasks and requirements which face to the supreme economic educational establishments are considered and concern to vocational training of experts on economic cybernetics; contradictions which overcoming determines a urgency and expediency of the designated problematics are determined; directions of pedagogical researches for the decision of tasks in view are traced; historical stages of becoming of vocational training of experts on economic cybernetics are proved; and as modern features of curriculums for the given vocational training are covered